Information Filtering and Array Algorithms for Discrete-Time Markovian Jump Linear Systems - Terra, M.H.; Ishihara, J.Y.; Jesus, G. (IEEE transactions on automatic control, 2009)
This technical note develops information filter and array algorithms for a linear minimum mean square error estimator of discrete-time Markovian jump linear systems. A numerical example for a two-mode Markovian jump linear system, to show the advantage of using array algorithms to filter this class of systems, is provided.